The Impact of the Evil Side of the English Language on My Life as an Artist. (11th November 2022) - Baram, Halgurd A.
Abstract : Discussing the English language and its difficult imposition into Kurdish life in Iraqi Kurdistan, Baram positions the Kurdish language as the boundary that marks Kurdish cultural space. He places Kurdish speakers in a precarious interrelationship between globalization and its negative effects, the endangered nature of the Kurdish language and its preservation as key to the cultural survival of the Kurds, and the English language as a problematic tool, necessary for interactions with a global community but laden with imperialistic anti-Middle Eastern and anti-Islamic meanings.